CROSS-BORDER NARCOTIC DISTRIBUTION IN THE PERSPECTIVE OF INTERNATIONAL LAW: A NORMATIVE STUDY IN THE RIAU ISLANDS - Nicha Suwalla; Khairul Riza; Siti Nurkhotijah; Christiani Prasetiasari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Cross-border drug trafficking is a form of transnational crime that threatens legal stability and global security. The Riau Islands as a strategic border region of Indonesia faces serious challenges in combating this crime due to limited law enforcement capacity, geographic vulnerability, and weak coordination between countries. This study aims to analyze the effectiveness of international legal regulations on cross-border drug trafficking and evaluate the challenges of its implementation in the Riau Islands region. The method used is normative juridical with a legislative and conceptual approach based on literature studies. The results of the study indicate that the weak harmonization of international norms with national laws, as well as limited capacity for legal enforcement and diplomacy, are the main obstacles. Therefore, it is necessary to strengthen the implementation of international conventions, cross-country coordination, and develop national legal institutions to effectively address the challenges of cross-border drug crimes.